Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.110.152.1990
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Consolidation and Permeability at the Barbados Forearc

Abstract: Sediments cored from the Barbados Ridge accretionary complex at ODP Sites 671, 672, and 676 are progressively underconsolidated with depth. Very low measured intergranular permeabilities contribute substantially to the probable excess pore-water pressures that account for the underconsolidated behavior. The estimated pore pressures immediately overlying the incipient decollement at the reference site are nearly equal to the overburden stress. Data show that the pore fluids within the fine-grained sediments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 26 publications
10
71
0
Order By: Relevance
“…When presented in terms of OCR, the values are small, less than one (the normally consolidated state), and decrease with depth with OCRs of 0.4, 0.2, and 0.1. These values are comparable to those measured previously at Barbados from Leg 110 (Taylor and Leonard, 1990) and at other modern accretionary complexes (Moran et al, 1993;.…”
Section: Consolidationsupporting
confidence: 79%
See 2 more Smart Citations
“…When presented in terms of OCR, the values are small, less than one (the normally consolidated state), and decrease with depth with OCRs of 0.4, 0.2, and 0.1. These values are comparable to those measured previously at Barbados from Leg 110 (Taylor and Leonard, 1990) and at other modern accretionary complexes (Moran et al, 1993;.…”
Section: Consolidationsupporting
confidence: 79%
“…We develop a generalized function by compiling permeability data for the northern Barbados Ridge that are estimated from onedimensional consolidation tests from a previous study (Taylor and Leonard, 1990). The hydraulic conductivity data are presented as a function of void ratio and show two distinct generalized relationships (Fig.…”
Section: Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lower matrix permeabilities and possible excess pore pressure in certain sedimentary units (Leonard, 1991) appear to channel fluid through more permeable, tectonically fractured lithologies. The low water content of the chalk below 200 mbsf at Site 829 is approximately half that of claystones and mudstones of similar depth at Site 671 in the Barbados complex (Mascle, Moore, et al, 1988;Leonard, 1989;Taylor and Leonard, 1990;Ask, 1991). This difference is due, in part, to sediments being incorporated into the complex from the DEZ that are more coarse-grained, less porous, and more permeable than the hemipelagic clay-dominated Barbados forearc.…”
Section: Dez Collision Zone Sites 827-831mentioning
confidence: 99%
“…Furthermore, previous researchers had inferred near-lithostatic pore pressures directly above the proto-decollement zone based on consolidation tests on cores (Taylor and Leonard, 1990). In contrast, previous studies, based on results from Deep Sea Drilling Project (DSDP) Leg 78a, concluded that sedimentation rates alone were not sufficient to produce overpressures (Marlow et al, 1984;Shi and Wang, 1986).…”
Section: A Major Objective Of Ocean Drilling Program (Odp) Legmentioning
confidence: 99%